1978
DOI: 10.1161/01.res.43.5.769
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changing metabolic rate on local blood flow control in the canine hindlimb.

Abstract: This study examined the effect of changing hindlimb metabolic rate on hindlimb blood flow control in anesthetized dogs. The hyperemias induced by graded levels of arterial hypoxia and the degree of steady state autoregulation evoked by changes in blood pressure were measured. Metabolic rate was increased above the resting value by direct electrical stimulation of hindlimb muscles at rates from 0.5 to 1.5 pulses/second, and in three dogs was reduced by cooling. In response to 6 minutes of arterial hypoxia, hind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

1983
1983
2008
2008

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 19 publications
3
22
0
1
Order By: Relevance
“…During conditions of increased oxygen consumption, however, the hind-limb P-F relationship is predominantly autoregulatory. These findings support the concept enunciated by Goodman et al (1978), that skeletal REGULATION OF BLOOD FLOW muscle blood flow is not only regulated in accordance with tissue metabolic requirements, but that the precision of blood flow control is also influenced by the metabolic state of the tissue. The finding that autoregulation is readily demonstrable during 'resting' conditions in tissues that normally have a relatively high metabolic rate, such as the heart (Drake-Holland, Laird, Noble, Spaan & Vergroesen, 1984) and brain (Johnson, 1978), also supports this concept.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…During conditions of increased oxygen consumption, however, the hind-limb P-F relationship is predominantly autoregulatory. These findings support the concept enunciated by Goodman et al (1978), that skeletal REGULATION OF BLOOD FLOW muscle blood flow is not only regulated in accordance with tissue metabolic requirements, but that the precision of blood flow control is also influenced by the metabolic state of the tissue. The finding that autoregulation is readily demonstrable during 'resting' conditions in tissues that normally have a relatively high metabolic rate, such as the heart (Drake-Holland, Laird, Noble, Spaan & Vergroesen, 1984) and brain (Johnson, 1978), also supports this concept.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies also demonstrated that the efficiency of hind-limb autoregulation increased with increases in metabolism (Stainsby, 1962;Jones & Berne, 1964a;Goodman et al 1978;Granger et al 1976). Granger et al (1975) have proposed a two component control system that explains how the efficiency of autoregulation and the rate of metabolism could be coupled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in brain, Ca O 2 is a critical variable in these tissues. For example, blood flow to muscle increases nonlinearly with O 2 desaturation and O 2 demand (9). The relatively large but variable increase in skeletal muscle flow (24.5 Ϯ 11.6 ml · min Ϫ 1 · 100 g Ϫ1 ) at 50% O 2 desaturation (Table 4) in the anemic group probably reflects the nonlinear response to Ca O 2 and the interanimal variability in Ca O 2 at this severe level of combined hypoxic and anemic hypoxia.…”
Section: H1940mentioning
confidence: 94%
“…1989. pability. as in adult dogs [3,4], and that blood flow would be redistributed to a work ing limb from the intestinal and renal circu lations. as during induced isometric contrac tion in adult dogs [5] or cats [6].…”
Section: Introductionmentioning
confidence: 99%